POLES, POTLATCHING, AND PUBLIC AFFAIRS: The Use of Aboriginal Culture in Development - McDonald, James A. (Culture, 1990)
In the summer of 1987 the Tsimshians of the village of Kitsumkalum in northwestern British Columbia raised three totem poles, a massive undertaking that enabled them to demonstrate the strength of their community and the political potency of their leaders to mobilize support for their goals. Today, aboriginal culture is being used as a resource to devise creative strategies for asserting or negotiating a social and political status quo. The pole raising was a means for these Tsimshians to restructure their mode of political expression and important aspects of their social organization along tradition lines. This paper examines how aboriginal culture was used to contextualize and negotiate policy issues critical to the community: land claims, self-government, and economic development.